Social networks and subjective wellbeing of adults in a Housing First program. Issue 1 (22nd March 2021) - Addo, Reuben; Yuma, Paula; Barrera, Irán; Layton, Danielle
Abstract: This study explored the social network properties and the correlates between social networks and subjective wellbeing of adults ( N  = 80) in a Housing First (HF) program. Using structured interviews, participants' social network properties were assessed. Bivariate correlations and backward multiple regression analyses were conducted to determine the association between social networks and subjective wellbeing. Findings indicate a combination of years of homelessness, years in housing, frequency of contact, intimate relationship, and perceived social support significantly predicted subjective wellbeing ( F (5, 74) = 2.74, p  = 0.025). While perceived social support was positively associated with subjective wellbeing, frequency of contact was negatively associated with subjective wellbeing. It is recommended that service providers develop strengths‐focused perspectives of the social networks of HF residents as potential contributors to subjective wellbeing. Service providers may need to pay more attention to HF residents with frequent contacts with network members, as they may have more distress.